2012
DOI: 10.1128/iai.05734-11
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus suis Capsular Polysaccharide Inhibits Phagocytosis through Destabilization of Lipid Microdomains and Prevents Lactosylceramide-Dependent Recognition

Abstract: Streptococcus suis type 2 is a major swine pathogen and a zoonotic agent, causing meningitis in both swine and humans. S. suis infects the host through the respiratory route, reaches the bloodstream, and persists until breaching into the central nervous system. The capsular polysaccharide (CPS) of S. suis type 2 is considered a key virulence factor of the bacteria. Though CPS allows S. suis to adhere to the membrane of cells of the immune system, it provides protection against phagocytosis. In fact, nonencapsu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 53 publications
(108 reference statements)
2
43
1
1
Order By: Relevance
“…This result is in accordance with previous in vitro findings of different groups showing that unencapsulated S. suis mutants are killed by different immune cells in the presence of inactivated serum (19,20,28). Interestingly, it has been shown that the capsule inhibits phagocytosis by macrophages through destabilization of lipid microdomains (38). This complement-independent immune evasion function of the capsule might, at least partially, explain the attenuation of the unencapsulated mutant in complement-deficient mice.…”
Section: Discussionsupporting
confidence: 81%
“…This result is in accordance with previous in vitro findings of different groups showing that unencapsulated S. suis mutants are killed by different immune cells in the presence of inactivated serum (19,20,28). Interestingly, it has been shown that the capsule inhibits phagocytosis by macrophages through destabilization of lipid microdomains (38). This complement-independent immune evasion function of the capsule might, at least partially, explain the attenuation of the unencapsulated mutant in complement-deficient mice.…”
Section: Discussionsupporting
confidence: 81%
“…In recent years, several virulence-associated biomarkers, such as CPS, muramidase-released protein, and extracellular factor, have been used for the detection of S. suis 2 infection. However, whether these factors are associated with bacterial pathogenicity remains controversial (32,33). The identification of 89K PAI is an important factor for evaluating S. suis 2 virulence.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of oxidation of the sialic acid (Neu5Ac) residues was assessed by gas chromatography (GC) analysis of the peracetylated methyl glycosides adapted from a previously described method (32). Briefly, oxidized CPS (0.4 mg) was reduced by treatment with 100 l of NaBH 4 (10 mg/ml) in water for 1 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%